Exploring the interplay between formal and relational governance in cross-border inter-firm relationships - Bosley, Gabriel (2021)
This thesis explores the interplay of formal (contractual and operational) governance, and relational governance of interfirm relationships. Using a theoretical framework drawing on resource-dependency theory, transaction costs, and social exchange theory, this explorative study reviews the literature on formal and relational governance of interfirm relationships, and subsequently analyses qualitative primary data from in-depth interviews conducted with informants from a small transportation and logistics firm using thematic analysis. Results are discussed and conclusions drawn from the analysis in this explorative study, which contributes its small part to the growing research interest on the topic.